Use of ecotoxicological modelling in Imboassica Lagoon, Macaé – RJ: a brief analysis - Souza, Nikolas Gomes Silveira de (2020)
The influence of metals in water bodies may generate damage to the aquatic biota, thus, effective methods for predicting these compounds and their maximum allowed concentrations are important to ensure environmental stability. The purpose of this work was to collect water samples in Imboassica Lagoon, in the summer of 2019, to obtain the chemical parameters, which were inserted in the Biotic Ligand Model program (BLM WindWard Software 2.1) in order to obtain copper acute toxicity results, using the fish Onchorhynchus mykiss as model organism. Toxicity (LC50) ranged from 23.14 µg.L-1 to 758.94 µg.L-1 resulting in a Water Quality Criteria (WQC) of 354,61 ± 163,39 μg.L-1. The results showed BLM as a tool compatible with the manager's need to obtain fast and accurate data on limit concentration of trace metals in the aquatic environment in order to contribute to the principles of sustainability.